SAFETY MECHANISMS FOR ELIMINATION OF THE CONSEQUENCES OF TRANSBOUNDARY EMERGENCIES - Eshnazarov A. B; Nazirzhonov S. A; Shamansurov S. S (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses ways to improve the mechanisms for ensuring security in the elimination of cross-border emergencies.